0112 First Night Effect on Sleep and Heart Rate in Adolescent Boys and Girls: Findings from the NCANDA Study. (12th April 2019) - Yüksel, Dilara; Smith, Ellen; Lim, Yun Qi; Goldstone, Aimee; Claudatos, Stephanie; Forouzanfar, Mohamad; Alschuler, Vanessa; Gil, Maureen; Colrain, Ian M; Prouty, Devin; Zambotti, Massimiliano de; Baker, Fiona
Abstract: Introduction: Women are more vulnerable than men to the development of insomnia disorder, with the sex difference emerging during adolescence. Underlying physiological mechanisms are unknown, although upregulation of the autonomic nervous system (ANS) during sleep is strongly implicated in the pathophysiology of insomnia and may be critical in its development in adolescent girls. ANS flexibility is particularly important for adaptive stress responses. The first night in the laboratory is considered a stressful condition and participants who are more sensitive to this effect may be at greater risk for insomnia. Here, we examined possible sex differences in the first night effect on HR and sleep variables in healthy adolescents. Methods: We compared polysomnographic (PSG) variables and nocturnal heart rate (HR) profiles between the first night in the laboratory (adaptation night) and a subsequent, non-consecutive overnight PSG (recording night) in 65 healthy adolescents (35 male). Participants were part of the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) cohort at SRI International and were aged between 12 and 19 years (M=15.23, SD=2.04). Results: Both male and female adolescents had a significantly higher HR at the beginning of the adaptation night than on the recording night (p<.05). HR showed the expected nocturnal decline during both overnights, however, in girls, the HR curve was shifted upwards across the adaptation night relative to the recording night. Differently, in boys, the differences in HR between the adaptation and recording nights diminished across the night (p <.05). Comparisons of sleep architecture showed that sleep efficiency tended to be lower during adaptation in all participants. Conclusion: Both adolescent boys and girls showed evidence of a first night effect, particularly for nocturnal HR. However, in girls, the effect is prolonged across the night. Longitudinal data from NCANDA will be able to examine further whether sex differences in stress-related ANS functioning predict different trajectories in the development of insomnia. Support (If Any): This study was supported by the National Consortium on Alcohol and NeuroDevelopment in Adolescence (NCANDA); AA021696 (IMC+FCB)